2021
DOI: 10.1093/femsle/fnab076
|View full text |Cite
|
Sign up to set email alerts
|

Unusual high prevalence of antibodies to hepatitis E virus in South Brazil

Abstract: Hepatitis E virus (HEV) is worldwide distributed and might cause acute or chronic hepatitis mainly in immunocompromised individuals. In previous studies we found a high prevalence of antibodies to HEV within blood donors in south Brazil and also within backyard-raised pigs. Here we aimed to investigate the prevalence of anti-HEV antibody and HEV RNA within the general population from three major municipalities (Caxias do Sul, Passo Fundo and Santa Maria) in south Brazil. A total of 3,000 blood samples were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“… 14 A previous study in the South region including blood donors performed with the same commercial assay reported a HEV prevalence of 18.7%, 6 and another study reported a prevalence greater than 55% using an indirect in-house ELISA assay. 15 Therefore, consumption of raw or undercooked pork meat seems to be the main route of HEV transmission in Brazil and our results support this evidence as most of the anti-HEV positive participants declared being born in regions with high consumption of pork meat.…”
supporting
confidence: 80%
“… 14 A previous study in the South region including blood donors performed with the same commercial assay reported a HEV prevalence of 18.7%, 6 and another study reported a prevalence greater than 55% using an indirect in-house ELISA assay. 15 Therefore, consumption of raw or undercooked pork meat seems to be the main route of HEV transmission in Brazil and our results support this evidence as most of the anti-HEV positive participants declared being born in regions with high consumption of pork meat.…”
supporting
confidence: 80%
“…The highest anti-HEV positivity was found in Passo Fundo (65.5%), followed by Caxias do Sul (57.4%) and Santa Maria (54.4%) citizens. The authors could not point out a specific risk factor distinguishing the studied population from other subsets from the same region [ 81 ]. For example, the consumption of pork and pork-derived food stuff (not rarely undercooked) is not an exclusive characteristic of the Rio Grande do Sul (RS) population but also a food custom of the Paraná (PR) and Santa Catarina (SC) states.…”
Section: Hev Prevalence In the Brazilian Populationmentioning
confidence: 99%
“…Although most commercial swine farming and pork-derivative food processing in Brazil are centralized in the three southern states, consuming raw or undercooked meat or pork liver was not significantly associated with higher HEV prevalence; the only factor significantly associated with the outcome was living in a rural area, as shown for blood donors from Rio Grande municipality [ 11 ]. Nevertheless, the dietary preference for pork meat and pork-derivative food-stuff is not the only source of infection, as vegetables and fruits can be contaminated by pork manure spreading on soil (as a fertilizer) [ 81 ]. Nevertheless, only a few cross-sectional studies have addressed questions regarding HEV foodborne transmission since most of them analyzed samples from their biorepositories or provided by other research groups into the scope of unrelated projects.…”
Section: Hev Prevalence In the Brazilian Populationmentioning
confidence: 99%
“…In the state of Rio Grande do Sul, Pandolfi et al [ 29 ] reported a 40.25% prevalence of anti-HEV antibodies among blood donors. Another study confirmed high HEV seroprevalence in the general populations of three municipalities in Rio Grande do Sul, reaching 55.4%, 57.4%, and 65.5% [ 30 ].…”
Section: Introductionmentioning
confidence: 85%
“…These authors reported that none of the 175 individuals tested positive for HEV [ 31 ]. Studies on the general population and blood donors from the southern region of Brazil indicated some of the highest rates of HEV seroprevalence in the country, ranging between 40% and 65% [ 29 , 30 , 40 ]. We found an HEV seroprevalence of 14.2% in the rural population of Rondônia, which is comparable to another finding of 12.9% in a rural settlement in the state of Acre in the Brazilian Amazon region [ 24 ].…”
Section: Discussionmentioning
confidence: 99%